The Role of microRNA-133 in Hemocyte Proliferation and Innate Immunity of Scylla paramamosain - Zhang, Yunfei; Lai, Yongyong; Zhou, Xiujuan; Zhu, Fei (Frontiers in Immunology, 2022)
MicroRNAs (miRNAs) are important signaling regulators that are involved in regulating the innate immunity of crustacean. However, few studies focus on the role of crustacean miRNAs in the cellular immunity have been reported. In this study, we showed that the expression of miR-133 was significantly up-regulated in the mud crab Scylla paramamosain after infection by white spot syndrome virus (WSSV) or Vibrio parahaemolyticus. The anti-miRNA oligonucleotide AMO-miR-133 was used to knock down miR-133 expression in S. paramamosain. The number of WSSV copies increased significantly in WSSV-infected crabs after miR-133 knockdown. Knockdown of miR-133 also enhanced the mortality rates of WSSV-infected and V. parahaemolyticus-infected mud crabs, and it significantly enhanced the expression of the astakine, which was confirmed by real-time quantitative PCR and western blot analysis. The data also indicate that miR-133 may affect hemocyte proliferation in S. paramamosain by regulating astakine expression. miR-133 Knockdown enhanced the apoptosis or phagocytosis of crab hemocytes, and increased the mortality of mud crabs after WSSV or V. parahaemolyticus infection. These results indicate that miR-133 is involved in the host immune response to WSSV and V. parahaemolyticus infection in mud crabs. Taken together, our research provides new insights for the control of viral or vibrio diseases in S. paramamosain.